ChemInform Abstract: 183W INADEQUATE 2D NMR Spectroscopy of Hetero Arsenato‐Phosphato‐Tungstate PV/AsV Substitution in Dawson‐Type α‐[AsxP2—xW18O62] 6‐ (x = 0—2) and α‐[H4AsyP1—yW18 O62]7‐ (y = 0, 1). Issue 31 (5th August 2014) - Haouas, Mohamed; Mbomekalle, Israel‐Martyr; Vila, Neus; de Oliveira, Pedro; Taulelle, Francis
Abstract The Dawson‐type arsenato‐phosphato tungstates of title are investigated by 183W and 31P NMR spectroscopy.